Wide-band slot antenna fed by coplanar waveguide for WLAN applications - Kueathaweekun, W.; Puntheeranurak, S.; Benjangkaprasert, C.; Anantrasirichai, N.; Wakabayashi, T. (My University, 2009)
This paper presents the slot antenna fed by coplanar waveguide (CPW) for WLAN applications. The characteristics of an antenna are proposed and analyzed for instance return loss, bandwidth and far field radiation patterns. Simulation results of the proposed antenna show the impedance bandwidth, determined by-10 dB return loss, approximate 140 % (1.66-9.44GHz) of the center band. The radiation patterns are bi-directional, and maximum gain is 5.7 dBi at 5.0 GHz. The simulation results of the slot antenna are analyzed by using IE3D Software.
Keywords: Coplanar waveguid; Slot antenna; Tuning stub; Wide-band antenna